Leukoencephalopathy due to variants in GFPT1-associated congenital myasthenic syndrome. (5th February 2019) - Helman, Guy; Sharma, Suvasini; Crawford, Joanna; Patra, Bijoy; Jain, Puneet; Bent, Stephen J.; Urtizberea, J. Andoni; Saran, Ravindra K.; Taft, Ryan J.; van der Knaap, Marjo S.; Simons, Cas
Abstract : Objective: To determine the molecular etiology of disease in 4 individuals from 2 unrelated families who presented with proximal muscle weakness and features suggestive of mitochondrial disease. Methods: Clinical information and neuroimaging were reviewed. Genome sequencing was performed on affected individuals and biological parents. Results: All affected individuals presented with muscle weakness and difficulty walking. In one family, both children had neonatal respiratory distress while the other family had 2 children with episodic deteriorations. In each family, muscle biopsy demonstrated ragged red fibers. MRI was suggestive of a mitochondrial leukoencephalopathy, with extensive deep cerebral white matter T2 hyperintense signal and selective involvement of the middle blade of the corpus callosum. Through genome sequencing, homozygous GFPT1 missense variants were identified in the affected individuals of each family. The variants detected (p.Arg14Leu and p.Thr151Lys) are absent from population databases and predicted to be damaging by in silico prediction tools. Following the genetic diagnosis, nerve conduction studies were performed and demonstrated a decremental response to repetitive nerve stimulation, confirming the diagnosis of myasthenia. Treatment with pyridostigmine was started in one family with favorable response. Conclusions: GFPT1 encodes a widely expressed protein that controls the flux of glucose into the hexosamine-biosynthesis pathway that produces precursors for glycosylation of proteins. GFPT1 variants and defects in other enzymes of this pathway have previously been associated with congenital myasthenia. These findings identify leukoencephalopathy as a previously unrecognized phenotype in GFPT1 -related disease and suggest that mitochondrial dysfunction could contribute to this disorder.